Higher circulating levels of chemokines CXCL10, CCL20 and CCL22 in patients with ischemic heart disease. (July 2016) - Safa, A.; Rashidinejad, H.R.; Khalili, M.; Dabiri, S.; Nemati, M.; Mohammadi, M.M.; Jafarzadeh, A.
Highlights: Serum levels of CXCL10, CCL20 and CCL22 were increased in patients with IHD. CXCL10 and CCL20 levels were higher in diabetic than non-diabetic patients. CCL22 levels were higher in dyslipidemic than non-dyslipidemic IHD patients. CCL22 levels were higher in obese than non-obese IHD patients. The SNPs rs4508917 and rs4359426 were associated with IHD. Abstract: Recruitment of leukocytes is one of the earliest events in the pathogenesis of ischemic heart disease (IHD) and chemokines play an important role in the migration of these cells into the inflammation sites. The aim of this study was to evaluate the CXCL10, CCL20 and CCL22 levels and the single nucleotide polymorphisms (SNPs) rs4508917, rs6749704 and rs4359426 in chemokine genes in patients with IHD to clarify any association. A total of 300 patients with IHD as having acute myocardial infarction (AMI; n = 100), stable angina (SA; n = 100) or unstable angina (UA; n = 100) and 100 healthy subjects as a control group were enrolled to study. Serum samples from all participants were tested for the CXCL10, CCL20 and CCL22 levels by using ELISA. The SNPs were determined by polymerase chain reaction–restriction length polymorphism (PCR–RFLP) method. The mean serum concentrations of CXCL10, CCL20 and CCL22 in AMI patients (395.97 ± 21.20 Pg/mL, 108.38 ± 10.31 Pg/mL and 1852.58 ± 205.77 Pg/mL), SA patients (405.48 ± 27.36 Pg/mL, 90.20 ± 7.69 Pg/mL and 2322.04 ± 231.23 Pg/mL) and UA patients (396.69 ± 22.79 Pg/mL, 141.87 ± 18.10 Pg/mL and 2754.89 ± 211.70 Pg/mL) were significantly higher than in the healthy group (179.38 ± 8.85 Pg/mL, 51.92 ± 4.62 Pg/mL and 451.82 ± 23.76 Pg/mL, respectively; P < 0.001). Similarly, the serum levels of CXCL10, CCL20 and CCL22 in total IHD patients (399.38 ± 13.77 Pg/mL, 113.49 ± 7.48 Pg/mL and 2309.84 ± 126.39 Pg/mL, respectively) were also significantly higher as compared with healthy subjects (P < 0.001). The serum levels of CCL20 and CCL22 in UA patients were significantly higher than those in SA and AMI patients, respectively (P < 0.01 and P < 0.003, respectively). The serum levels of CXCL10 and CCL20 in diabetic patients were significantly higher in comparison to non-diabetic patients (P < 0.05 and P < 0.02, respectively). The serum levels of CCL22 in dyslipidemic- and obese patients were also significantly higher in comparison with non-dyslipidemic- and non-obese patients, correspondingly (P < 0.05 and P < 0.01, respectively). There were no significant differences between men and women or between patients who treated with statin, aspirin, β-blockers or angiotensin converting enzyme (ACE) inhibitors and patients without mentioned treatment regarding the levels of chemokines. The frequency of the GG genotype at SNP rs4508917 in CXCL10 gene was higher, whereas the frequency of the AA genotype at SNP rs4359426 in CCL22 gene was lower in total patients with IHD as compared with healthy subjects (P < 0.04 and P < 0.002, respectively). These results showed that the higher levels of CXCL10, CCL20 and CCL22 were associated with IHD. The serum levels of chemokines may influence by the certain traditional risk factors of IHD and some studied SNPs, but did not influence by treatment and gender of patients.